2008
DOI: 10.1371/journal.pntd.0000293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Treatment with Ivermectin on the Prevalence and Intensity of Soil-Transmitted Helminth Infections

Abstract: BackgroundControl of soil-transmitted helminth (STH) infections relies on the periodic and long-term administration of anthelmintic drugs to high-risk groups, particularly school-age children living in endemic areas. There is limited data on the effectiveness of long-term periodic anthelmintic treatment on the prevalence of STHs, particularly from operational programmes. The current study investigated the impact of 15 to 17 years of treatment with the broad-spectrum anthelmintic ivermectin, used for the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 37 publications
4
55
2
2
Order By: Relevance
“…Moncayo and colleagues 23 conducted a similar study to this one in northeastern Ecuador in areas where IV had been distributed largely on a 6 month (semiannual) schedule as an intervention for onchocerciasis for 15 to 17 years. Their study showed a significant impact only on the prevalence and intensity of infection of Trichuris , finding no effect on either Ascaris or hookworm infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moncayo and colleagues 23 conducted a similar study to this one in northeastern Ecuador in areas where IV had been distributed largely on a 6 month (semiannual) schedule as an intervention for onchocerciasis for 15 to 17 years. Their study showed a significant impact only on the prevalence and intensity of infection of Trichuris , finding no effect on either Ascaris or hookworm infection.…”
Section: Discussionmentioning
confidence: 97%
“…14,21 A study by Ranque and colleagues 22 using quarterly IV therapy for a year found a significant decrease in the prevalence of STH infection after the first round of therapy, with no subsequent additional decrease. Moncayo and colleagues 23 studied the impact of twice per year IV therapy in northeastern Ecuador on STH. However, no studies have been done to look at the effect on the prevalence of STH following annual mass drug administration (MDA) with IV for onchocerciasis that occurs at approximately 40 million treatments per year in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Ivermectin has modest efficacy against hookworm compared with other STNs, 16,82 and MDA programs for onchocerciasis can alter the epidemiology of STN infections. 82,83 For example, in the study by Moncaya and others, 82 a reduction in T. trichiura prevalence because of ivermectin therapy was associated with a marked increase in the prevalence of hookworm. Although administration of albendazole was associated with an overall egg reduction rate of 81% in the study population, treatment failed to eliminate fecal egg excretion in more than one-third (39%) of subjects on follow-up exam.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Mass treatment with ivermectin in resource-poor communities has already been shown to significantly reduce the prevalence of intestinal helminths and of cutaneous infestation 19 For soil-transmitted helminths, repeated ivermectin mass treatments have been shown to reduce transmission as well. 20 With this study we have demonstrated that an intervention consisting of household-wide treatment with ivermectin effectively reduces within-household transmission of head lice. These findings suggest that mass treatment with ivermectin not only reduces the prevalence of head lice infestation in treated individuals, but also benefits untreated members of the community by reducing transmission.…”
Section: Discussionmentioning
confidence: 70%
“…The median infestation-free period in the intervention group was 24 days (interquartile range, IQR: 11-45), as compared to 14 days (IQR: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] in the control group (P = 0.01). Household-wide treatment with ivermectin proved significantly more effective among boys than among girls (P = 0.005).…”
mentioning
confidence: 99%